Phase II/III trial of a pre‐transplant farnesyl transferase inhibitor in juvenile myelomonocytic leukemia: A report from the Children's Oncology Group. Issue 4 (8th December 2014) - Stieglitz, Elliot; Ward, Ashley F.; Gerbing, Robert B.; Alonzo, Todd A.; Arceci, Robert J.; Liu, Y. Lucy; Emanuel, Peter D.; Widemann, Brigitte C.; Cheng, Jennifer W.; Jayaprakash, Nalini; Balis, Frank M.; Castleberry, Robert P.; et al.
<x xml:space="preserve">Abstract</x> Background Juvenile myelomonocytic leukemia (JMML) is not durably responsive to chemotherapy, and approximately 50% of patients relapse after hematopoietic stem cell transplant (HSCT). Here we report the activity and acute toxicity of the farnesyl transferase inhibitor tipifarnib, the response rate to 13‐cis retinoic acid (CRA) in combination with cytoreductive chemotherapy, and survival following HSCT in children with JMML. Procedure Eighty‐five patients with newly diagnosed JMML were enrolled on AAML0122 between 2001 and 2006. Forty‐seven consented to receive tipifarnib in a phase II window before proceeding to a phase III trial of CRA in combination with fludarabine and cytarabine followed by HSCT and maintenance CRA. Thirty‐eight patients enrolled only in the phase III trial. Results Overall response rate was 51% after tipifarnib and 68% after fludarabine/cytarabine/CRA. Tipifarnib did not increase pre‐transplant toxicities. Forty‐six percent of the 44 patients who received protocol compliant HSCT relapsed. Five‐year overall survival was 55 ± 11% and event‐free survival was 41 ± 11%, with no significant difference between patients who did or did not receive tipifarnib. Conclusions Administration of tipifarnib in the window setting followed by HSCT in patients with newly diagnosed JMML was safe and yielded a 51% initial response rate as a single agent, but failed to reduce relapse rates or improve long‐term overall survival. Pediatr Blood Cancer 2015;62:629–636. © 2014 Wiley Periodicals, Inc.